The West Wing. The complete first season [videorecording (DVD)] - Graves, Alex; Sheen, Martin; Spencer, John, 1946-2005; Lowe, Rob; Channing, Stockard; Janney, Allison (Warner Home Video, 2003)
Headed by President Josiah Bartlet, demonstrates that office politics are the same everywhere; things just have greater repercussions when your office happens to be the White House. Stories surround the President; his deputy communications director Sam Seaborn; his beleaguered press secretary, C.J. Cregg; the chief of staff, recovering boozehound Leo McGarry, who sacrifices his marriage to his career. Among the global crises Bartlet must finesse are a nuclear showdown between India and Pakistan, an American plane shot down by terrorists, and another downed U.S. plane in Iraq.